2006
DOI: 10.1038/sj.onc.1209358
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nur77 nuclear export by c-Jun N-terminal kinase and Akt

Abstract: Proapoptotic nuclear receptor family member Nur77 translocates from the nucleus to the mitochondria, where it interacts with Bcl-2 to trigger apoptosis. Nur77 translocation is induced by certain apoptotic stimuli, including the synthetic retinoid-related 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphthalenecarboxylic acid (AHPN)/ CD437 class. In this study, we investigated the molecular mechanism by which AHPN/CD437 analog (E)-4-[3-(1-adamantyl)-4-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC) induces Nur77 nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 74 publications
9
138
2
Order By: Relevance
“…(Magnifications: B-D, ϫ4,000. ) ptotic protein Nur77 from the nucleus (28,29). Consistent with this possibility, JNK protein is concentrated in the nucleus of Xenopus embryos (Fig.…”
Section: Jnk Inhibits Wnt͞␤-catenin-mediated Transcription and Exportssupporting
confidence: 67%
See 1 more Smart Citation
“…(Magnifications: B-D, ϫ4,000. ) ptotic protein Nur77 from the nucleus (28,29). Consistent with this possibility, JNK protein is concentrated in the nucleus of Xenopus embryos (Fig.…”
Section: Jnk Inhibits Wnt͞␤-catenin-mediated Transcription and Exportssupporting
confidence: 67%
“…It has been shown that JNK induces nuclear export of PDX-1 and Nur77 (28,29). A recent study also showed that JNK phosphorylates Nup214, a subunit of the nuclear pore complex (31).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blotting-Cell lysates were boiled in SDS sample buffer, resolved by SDS-PAGE (8 or 12.5% polyacrylamide), and transferred to nitrocellulose (35,36,41). After transfer, the membranes were blocked in 5% milk in TBST (10 mM Tris-HCl, pH 8.0, 150 mM NaCl, and 0.05% Tween 20) for 30 min and incubated with primary antibody in 5% milk in TBST for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…TR3 is a hyperphosphorylated protein that can be phosphorylated by a number of protein kinases including ERK2 (Katagiri et al, 2000;Slagsvold et al, 2002;Jacobs et al, 2004) and JNK1 (Kolluri et al, 2003;Han et al, 2006;Liu et al, 2007). Several studies have highlighted the importance of the ERK signal pathway in controlling TR3 translocation (Katagiri et al, 2000;Jacobs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%